PERTANGGUNG JAWABAN HUKUM ATAS PENCEMARAN LINGKUNGAN DALAM PENGELOLAAN TPA\TPST CIPEUCANG: ANALISIS PUTUSAN NO 194/Pdt.G/2026/PN Tng - Farida Nurun Nazah; Siti Aisyah; Athaya Alghaniyyu Rahmatulloh; Rama Fachreza Aleaputra; Hielda Rahmawati; Zahra Ramadhanty Drajat; Zulpan Syahputra Gulo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the legal responsibility of the parties involved in environmental pollution resulting from the management of the Cipeucang landfill (TPA/TPST), as well as to assess the effectiveness of the environmental recovery measures ordered in the court decision. The research employs a normative juridical approach by examining relevant laws and regulations, as well as court rulings related to the case.The findings indicate that the Government of South Tangerang City and the related parties were found to have committed onrechtmatige overheidsdaad (unlawful acts by the government). In its decision, the court applied the polluter pays principle by imposing liability on the parties responsible for the environmental pollution to compensate for damages and to carry out environmental recovery measures. The novelty of this study lies in its analysis of the combined application of compensation and environmental recovery as forms of legal liability in Decision Number 194/Pdt.G/2026/PN Tng, an issue that has received limited attention in previous studies. The forms of legal responsibility imposed include the obligation to cease the unlawful conduct, pay compensation, and undertake environmental restoration measures. However, the effectiveness of the court-ordered environmental recovery has not yet been optimal due to technical implementation challenges, inadequate supervision, and the lengthy process required to restore the damaged environment.Therefore, stronger oversight and greater commitment are necessary to ensure that the implementation of court decisions leads to effective environmental recovery in line with the objectives of environmental protection.